Does Co-occurred Cerebral Palsy Change the Prognosis of West Syndrome? - Nagy, Eszter; Farkas, Nelli; Hollódy, Katalin (Neuropediatrics, 2020)
Aim We aimed to examine the occurrence of cerebral palsy (CP) in children with West syndrome (WS), to estimate the possible causative factors by analyzing the neuroimaging examinations of patients, to evaluate their cognitive/motor function and epileptic status and to compare the prognosis of children with double pathology of WS and CP and of those without CP.Methods The clinical and magnetic resonance imaging (MRI) data of 62 patients with West syndrome were evaluated. A total of 39 of 62 patients (63%) suffered from CP (CP group). The non-CP group included 23 patients.Results Abnormal MRI was found in 55/62 (89%) patients. Main anomalies were: brain malformation (21), hypoxic-ischemic encephalopathy (13), cerebrovascular insult (8), infection (7), and other anomalies (6). In the CP group, the most common MRI abnormalities included pre/perinatal hypoxia/ischemia, brain malformation, cerebrovascular insult, and infection. In the non-CP group, brain malformations were the most frequent. Significantly more negative MRIs were found in the non-CP group. More than 60% of the patients were severely cognitively impaired, almost 90% of them had CP. Not only the occurrence of intellectual disability was lower in the non-CP group, but its severity was milder as well. A total of 78% of the children with CP had a very severe motor disability. Fifty-four percent in the CP and 67% in the non-CP group had therapy-resistant epilepsy.Conclusion WS has an especially unfavorable prognosis: cerebral anomaly was confirmed in 89% of our patients. CP was present in almost two-thirds of the children with WS, most of them had severe cognitive and motor deficits.
Keywords: West syndrome; infantile spasm; cerebral palsy; etiology; MRI; walking ability